On the determination of the quasiparticle scattering rate in unconventional superconductors by microwave surface impedance
As found from numerous microwave experiments on the unconventional Fe-based superconductors, the temperature dependence of the quasiparticle scattering rate t–1 cannot be accurately described within the framework of standard Drude module in the popular approximation of wt